New Species of Polypedates (Anura: Rhacophoridae) from the Western Ghats, Southwest India - Das, I.; Dutta, Sushil K. (The Society for the Study of Amphibians and Reptiles, 2006)
A new species of rhacophorid of the genus Polypedates is described on the basis of three adult males and a metamorph from Kerala State, southwestern India. The new species is related to Polypedates cruciger from Sri Lanka, Polypedates pseudocruciger from the Western Ghats of India and Polypedates maculatus from northern Sri Lanka and mainland south Asia. It is diagnosed by the following characters: adult male SVL to 55.1mm; unpigmented nuptial pads on dorsal surfaces of Fingers I and II; vomerine teeth set obliquely between choanae; fingers with rudimentary webbing; no dermal fold along forearm; webbing on Toe III reaching disks at tip of digit; absence of a conical lingual papilla; skin of forehead free; snout lacking a dermal flap; heel lacking a cutaneous spur; and a dark hour-glass-shaped pattern on dorsum.